2012
DOI: 10.1542/peds.2011-1804
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Gender Nonconformity: A Risk Indicator for Childhood Abuse and Posttraumatic Stress in Youth

Abstract: WHAT'S KNOWN ON THIS SUBJECT: Childhood gender nonconformity has been associated with poorer relationships with parents, but it is unknown if childhood gender nonconformity is associated with childhood abuse or with posttraumatic stress disorder. WHAT THIS STUDY ADDS:We identify gender nonconformity before age 11 years as a risk indicator for physical, sexual, and psychological abuse in childhood and lifetime probable posttraumatic stress disorder in youth. abstract OBJECTIVES: Childhood gender nonconformity h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
176
1
10

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 223 publications
(195 citation statements)
references
References 56 publications
8
176
1
10
Order By: Relevance
“…27 GN youth are at increased risk for a number of adverse mental health and medical outcomes, including anxiety, depression, suicidality, oppositional defiance, lower school performance, nonsuicidal self-injury, drug abuse, and alcohol abuse. 6,[28][29][30][31] Of note, the measures used in some of the research studies have been questioned because they often use binary measures of gender; rely heavily on parent reports, which may be biased; and may fail to integrate measures of social stigma or rejection that may be related to if not causal of the psychological difficulties reported. Many of these outcomes are likely due to the social rejection experienced by GN youth along with the lack of family support for their gender nonconformity.…”
Section: Gender Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…27 GN youth are at increased risk for a number of adverse mental health and medical outcomes, including anxiety, depression, suicidality, oppositional defiance, lower school performance, nonsuicidal self-injury, drug abuse, and alcohol abuse. 6,[28][29][30][31] Of note, the measures used in some of the research studies have been questioned because they often use binary measures of gender; rely heavily on parent reports, which may be biased; and may fail to integrate measures of social stigma or rejection that may be related to if not causal of the psychological difficulties reported. Many of these outcomes are likely due to the social rejection experienced by GN youth along with the lack of family support for their gender nonconformity.…”
Section: Gender Developmentmentioning
confidence: 99%
“…Many of these outcomes are likely due to the social rejection experienced by GN youth along with the lack of family support for their gender nonconformity. 29,[31][32][33] The manifestations of anxiety, depression, or self-harm can also be caused by distress from the body not matching one' s affirmed gender. Recent studies have indicated that when social supports are put in place that recognize and affirm the child' s gender nonconformity, the symptoms are significantly alleviated with improved mental health outcomes.…”
Section: Gender Developmentmentioning
confidence: 99%
“…First, childhood trauma, including psychological, physical and sexual abuse are more likely to be experienced amongst sexual minority status groups (Austin et al, 2008;Hatzenbuehler, 2011;Roberts et al, 2010;Roberts, Glymour & Koenen, 2013;Wilson & Widom, 2010), and abuse in childhood is linked to greater victimisation in adulthood (Balsam et al, 2005) and to revictimisation (Balsam, Levahot & Beadnell, 2011). Furthermore, victimisation from abuse in childhood is also associated with gender nonconformity behaviours in children (Roberts, Rosario, Corliss, Koenen & Austin, 2012), and sexual orientation victimisation with gender atypicality amongst adolescents (D'Augelli, Grossman & Starks, 2006). Second, minority stress in the form of the sexual prejudice (Herek, 2000;Savin-Williams, Pardo, Vrangalova, Mitchell & Cohen, 2010;Hatzenbuehler, 2009;Meyer, 2003), stigma and social exclusion sexual minority status groups are exposed to can have a deleterious effect on psychological and physical health, and is associated with risk-taking behaviours linked to greater victimisation risk (Boehmer, Miao, Linkletter & Clark, 2012;Bontempo & D'Augelli, 2002;Cochran, 2001;Cochran & Mays, 2009;D'Augelli, 2003;Goodenow, Netherland & Szalacha, 2002;Hatzenbuehler, 2009;Meyer, 2003;Paul et al, 2002;Robin et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…It may be that the greater engagement in weight restriction behaviors noted among sexual minority males relative to heterosexual males 14 is tied to greater gender nonconformity (ie, greater conformity to femininity norms rather than masculinity norms) among sexual minority males. 23 Alternatively, sexual minority females are generally more gender nonconforming than heterosexual females, 25 yet sexual minority females have also been found to be more vulnerable to laxative use for weight loss. 14,15 Examining the unique and interactive effects of gender conformity and sexual orientation can help clarify previous findings.…”
mentioning
confidence: 99%